2017
DOI: 10.1002/cam4.1293
|View full text |Cite
|
Sign up to set email alerts
|

AKT3 drives adenoid cystic carcinoma development in salivary glands

Abstract: Salivary gland cancer is an aggressive and painful cancer, but a rare tumor type accounting for only ~0.5% of cancer cases. Tumors of the salivary gland exhibit heterogeneous histologic and genetic features and they are subdivided into different subtypes, with adenoid cystic carcinomas (ACC) being one of the most abundant. Treatment of ACC patients is afflicted by high recurrence rates, the high potential of the tumors to metastasize, as well as the poor response of ACC to chemotherapy. A prerequisite for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…It is intriguing to note that PI3K/AKT/mTOR pathways would contribute to cancer cell proliferation in head and neck squamous cell carcinoma (HNSCC), possibly serving a pro-tumorigenic function [ 48 ]. In accordance with the above HNSCC study, the most common malignant salivary gland neoplasm, adenoid cystic carcinoma, exhibits similar characteristics in the PI3K/AKT/mTOR axis [ 49 ]. One therapeutic method for tumors was to target the PI3K/AKT/mTOR pathways with an inhibitor [ 50 ].…”
Section: Discussionsupporting
confidence: 53%
“…It is intriguing to note that PI3K/AKT/mTOR pathways would contribute to cancer cell proliferation in head and neck squamous cell carcinoma (HNSCC), possibly serving a pro-tumorigenic function [ 48 ]. In accordance with the above HNSCC study, the most common malignant salivary gland neoplasm, adenoid cystic carcinoma, exhibits similar characteristics in the PI3K/AKT/mTOR axis [ 49 ]. One therapeutic method for tumors was to target the PI3K/AKT/mTOR pathways with an inhibitor [ 50 ].…”
Section: Discussionsupporting
confidence: 53%
“…AKT3 is a homologous gene that belongs to the serine/ threonine protein kinase AKT subfamily. Once AKT3 has been hyperactivated in tumorigenesis, it could be a vulnerable node to be targeted (Zboray, Mohrherr, Stiedl, Pranz, & Wandruszka, 2017). The expression and activation of AKT3 mediates cancer progression and controls cellular processes such as cell growth, proliferation, apoptosis, and invasion (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that NGF can activate PI3K/AKT pathway through phosphorylating AKT in SACC, thereby potentially stimulating scattering and migration of tumor cells which enhances the progression of PNI (60). Additionally, animal experiments have also shown that a high expression of Akt3 serves as a driving factor of salivary gland tumor progression (43). In addition, the NT-3/TrkC axis promotes the progression of PNI and the poor prognosis of SACC by regulating the interaction between SACC cells and SC.…”
Section: Ngf Family and Receptorsmentioning
confidence: 99%